Komunikasi Profetik Merawat Rohani Islam (Penyakit Hati) - Vionitas, Vina (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2020)
This study explores the concept of spiritual heart disease (qalbu) from an Islamic perspective and its healing process through prophetic communication. Prophet Muhammad SAW emphasized that the heart serves as the control center of the human body—if the heart is sound, the entire body is sound; if it is corrupt, the entire body is corrupt. A diseased heart tends to perceive truth as harmful and prefers falsehood and harm. This research employs content analysis by establishing study boundaries and utilizing primary sources such as the Qur’an and Hadith, alongside secondary sources in relevant Islamic literature. The findings reveal that heart disease arises from syubhat (doubt) and syahwat (desire), driven by factors such as shirk (polytheism), sinful behavior, heedlessness, turning away from Allah, and an excessive attachment to worldly matters. As a result, individuals lose their sense of guilt when committing sins. Prophetic communication serves as a healing method, modeled after the Prophet’s guidance to his followers. This includes strengthening spiritual connection with Allah through His names al-Hayyu and al-Qayyum, sincere acknowledgment of servitude, reliance on Allah (tawakkul), recitation of the Qur’an, seeking forgiveness (istighfar), repentance (taubah), spiritual striving (jihad), performing prayer (shalat), and fully surrendering one’s will to Allah SWT. This research contributes to enhancing spiritual awareness as a solution to the inner ailments of modern life. Keywords: heart disease, prophetic communication, qalbu, syubhat, syahwat